Multi -Objective Economic Dispatch Using Evolutionary Programming - Noor Azlan Bin Adnan (2023)
Economic dispatch (ED) is an optimization strategy to ensure power system operate in such an economic manner. This study focused on solving multi-objectives economic dispatch using Heuristic Optimization (HO) technique which is Multi-Objective Evolutionary Programming (MOEP). Increasing amount of total cost and total losses power system forcing developer to seek a plan to reduce the values. Therefore, this project proposed an algorithm to minimize total cost and total losses simultaneously and find the best adjustment for this economic dispatch problems. Weighted Sum Method (WSM) has been applied to find trade-off solution between both objectives. Two constraints used to increase performance of this project which are equality and inequality constraints. The practicable proposed method has been tested on IEEE 30 Bus RTS which demonstrated for three different case. Case study 1 will operate on normal operation, case study 2 will operate with 50% load increment and lastly, case study 3 will operate with 70% load increment. The designated algorithm of MOEP used MATLAB to run the simulations. The performance of MOEP for this project has been compared with other technique which is Artificial Immune System (AIS). The experimental result shows that MOEP dominates in all cases that have been tested. Hence, MOEP is admirable to provide high-quality solutions economic dispatch problems.